Intestinal Flora Imbalance Induced by Antibiotic Use in Rats - Tong G; Qian H; Li D; Li J; Chen J; Li X; Tan Z (Dove Medical Press, 2024)
Guojun Tong,1,2 Hai Qian,1 Dongli Li,2 Jing Li,2 Jing Chen,2 Xiongfeng Li,3 Zhenhua Tan1 1General Surgery, Huzhou Central Hospital, The Affiliated Central Hospital of Huzhou University, Huzhou, People's Republic of China; 2Central Laboratory, Huzhou Central Hospital, The Affiliated Central Hospital of Huzhou University, Huzhou, People's Republic of China; 3Orthopedic Surgery, Huzhou Central Hospital, The Affiliated Central Hospital of Huzhou University, Huzhou, People's Republic of ChinaCorrespondence: Zhenhua Tan, General Surgery, Huzhou Central Hospital, The Affiliated Central Hospital of Huzhou University, Sanhuan North Road 1558#, Huzhou, People's Republic of China, Email Tanzh99@163.comAim: This study aims to explore the effect of different doses of antibiotics on rats in order to observe alterations in their fecal microbiota, inflammatory changes in the colonic mucosa and four types of inflammatory markers in blood serum.Methods: Our methodology involved separating 84 female Sprague Dawley rats into groups A-G, with each group consisting of 12 rats. We collected the rat feces for analysis, using a distinct medium for bacterial cultivation and counting colonies under a microscope. On the 11th and 15th days of the experiment, half of the rats from each group were euthanized and 5 mL of abdominal aortic blood and colon tissues were collected. Inflammations changes of colon were observed and assessed by pathological Hematoxylin Eosin (HE) staining. Enzyme-linked immune sorbent assay (ELISA) was adopted for detecting C-reactive protein (CRP), IL-6, IL1-β and TNF-α.Results: Our findings revealed that the initial average weight of the rats did not differ between groups (p> 0.05); but significant differences were observed between stool samples, water intake, food intake and weight (p=0.009, < 0.001, 0.016 and 0.04, respectively) within two hours after the experiment. Additionally, there were notable differences among the groups in nine tested microbiota before and after weighting methods (all p< 0.001). There were no difference in nine microbiota at day 1 (all p> 0.05); at day 4 A/B (p=0.044), A/D (p< 0.001), A/E (p=0.029); at day 8, all p< 0.01, at day 11, only A/F exist significant difference (p< 0.001); at day 14 only A/D has difference (p=0.045). Inflammation changes of colon were observed between groups A-G at days 11 and 15. Significant differences between all groups can be observed for CRP, IL-6, IL1-β and TNF-α (p< 0.001).Conclusion: This study suggests that antibiotics administration can disrupt the balance of bacteria in the rat gut ecosystem, resulting in an inflammatory response in their bloodstream and inducing inflammation changes of colon. Keywords: antibiotics, imbalance of intestinal flora, Sprague Dawley rats, inflammatory bowel disease, IBD, colitis model